Impact of Corn Fiber on the Physicochemical/Technological Properties, Emotions, Purchase Intent and Sensory Characteristics of Gluten Free Bread with Novel Flours - Ricardo S. Aleman; Jhunior Abrahan Marcia Fuentes; Ajitesh Yadav; Shirin Kazemzadeh; Franklin Delcarca; Mallerly Sarmientos; Mehrdad Hasani-Azhdari; Ismael Montero-Fernández (Dietetics, 2023)
Gluten-free products present huge advantages for individuals with gluten intolerance or celiac disease. The most influential strategy to develop a product comparable to wheat-containing gluten products is to promote its nutritional and sensorial attributes. Recently, rice flour and teosinte flour were used to develop gluten-free bread. As a result, this work aimed to compare the physical/technological attributes of bread made with rice flour and teosinte flour with corn fiber fortification and examine consumer acceptance and purchase intent. An extreme vertices mixture design decided that a teosinte flour (43.4%), high protein white rice flour (55%), and high protein brown rice flour (1.6%) ratio of gluten-free flour mixture for bread was best based on the sensory attributes utilized for the desirability function methodology. After optimizing the gluten-free flour mixture, the bread was fortified with corn fiber under 1.7 g and 3.8 g per serving, and it was evaluated to examine its physical/technological attributes, consumer perception, liking, emotions, and purchase intent. Incorporating fiber into gluten-free bread impacted the color and texture, giving lighter and yellower colors with a firmer texture. Likewise, concerning health benefit claims, gluten-free bread with fiber claims only improves the purchase intent and overall liking of bread containing 1.7 g per serving of fiber. The flavor attribute was the main driver for consumers’ purchase decisions. This product could be beneficial for consumers who are seeking fiber in their diet.